Knowledge in rural transitions: Formal and informal underpinnings of land governance in Khorezm - Kristof Van Assche; Anna-Katharina Hornidge (University of Bonn, Center for Development Research (ZEF), 2012)
We analyze the shifting selections and roles of knowledge in rapidly evolving rural governance, exemplified by the complex transition of land governance in Khorezm, a province of Uzbekistan. Through a study of the evolution of various organizations involved in land governance at different spatial scales, we reconstruct the changing patterns of formality and informality in the organization and management of land in this irrigated rural area. These patterns, we argue, are crucial in understanding which forms of knowledge could and can play a role in spatial decisionmaking. It is further argued that a widening gap between formal and informal institutions, aggravated by the rhetorical persistence of Soviet planning mythologies, makes it increasingly hard to discern which knowledge plays a role in spatial decision-making. This situation is bound to hinder planning and development attempts involving the development and application of knowledge. While many observed mechanisms of knowledge selection seem specific to post-Soviet transition, we argue that they are present in every situation where planning mythologies and path-dependencies mark the evolution of rural governance, and that they ought to be studied in their own context before deciding which knowledge could drive development.
Keywords: 330; Knowledge; Formalities/Informalities; Land Governance; Uzbekistan; Central Asia